2021
DOI: 10.1177/21514593211004533
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Cognitive Impairment as a Perioperative Risk Factor in Patients Undergoing Total Knee Arthroplasty

Abstract: Background: The study assessed whether pre-existing cognitive impairment (CI) prior to elective total knee arthroplasty (TKA) is associated with worse postoperative outcomes such as delirium, in-hospital medical complications, 30-day mortality, hospital length of stay and non-home discharge. Methods: A retrospective database analysis from the NSQIP Geriatric Surgery Pilot Project was used. There was an initial cohort of 6350 patients undergoing elective TKA, 104 patients with CI were propensity score matched t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…POCD is more frequent and lasts longer in older patients following surgery under anesthesia, which may be mainly due to degenerative changes in the structure of the brain and a progressive decline in reserve function [36]. It is generally accepted that advanced age, especially pre-existing cognitive impairment, is associated with a high incidence of POCD [37,38]. Episodes of cerebral ischemia and hypoxia have been regarded as the most closely related to POCD among distinct etiological factors [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…POCD is more frequent and lasts longer in older patients following surgery under anesthesia, which may be mainly due to degenerative changes in the structure of the brain and a progressive decline in reserve function [36]. It is generally accepted that advanced age, especially pre-existing cognitive impairment, is associated with a high incidence of POCD [37,38]. Episodes of cerebral ischemia and hypoxia have been regarded as the most closely related to POCD among distinct etiological factors [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests that preoperative CI increases the risk of having poor postoperative functional outcomes 29. Similarly, a retrospective study reported that older patients with preoperative CI undergoing orthopedic surgery were at a greater risk of becoming partially or fully dependent on their activities of daily living than those without CI 53. In cardiac surgery, one study suggested that preoperative cognitive assessment would provide a more accurate prediction of reduced activities of daily living within 6 months of surgery than preoperative functional assessments 54…”
Section: Postdischarge Outcomes Associated With CImentioning
confidence: 99%
“…Postoperative delirium (POD) is a syndrome that can manifest in patients one to 3 days postoperatively [5]. This syndrome can have detrimental long-term effects on patients in addition to increased burden on the healthcare system [5]. POD is associated with increased postoperative complications, longer length of hospital stay and higher rates of discharge to an acute care facility [6].…”
Section: Brain Healthmentioning
confidence: 99%
“…This initiative was started to reduce the impact of preexisting cognitive deficits and optimize cognitive recovery in adults 65 and older undergoing surgery. Postoperative delirium (POD) is a syndrome that can manifest in patients one to 3 days postoperatively [5]. This syndrome can have detrimental long-term effects on patients in addition to increased burden on the healthcare system [5].…”
Section: Brain Healthmentioning
confidence: 99%